Can allogeneic hematopoietic cell transplant cure therapy-related acute leukemia?. Issue 1 (March 2019) - Madanat, Yazan F.; Gerds, Aaron T.
Abstract: Therapy-related myeloid neoplasms (t-MN) include both therapy-related myelodysplastic syndromes as well as therapy-related acute myeloid leukemia. These two entities were grouped together in the World Health Organization classification of AML due to having similarly poor outcomes and disease biology. Exposure to prior radiation therapy or chemotherapy for other malignant or benign conditions, namely autoimmune diseases or solid organ transplants, constitutes the principal risk factor to develop t-MN. Mechanisms for the development of t-MN include direct genotoxic damage from prior chemotherapy or radiation therapy exposure and the selection of pre-existing clones with malignant potential that are able to evolve with time and manifest as new cancers. Patients with t-MN are generally considered high-risk at the time of diagnosis and are commonly referred for consideration of an allogeneic hematopoietic cell transplantation, however, this patient population poses unique challenges, and little is known about the ideal sequence and timing of treatment. In this review, we summarize the data pertaining to transplant options, focusing on patient and disease characteristics in which transplantation may be most useful and populations where non-transplant options may also be considered.